Combination of Emoji and Text in Musicians’ Twitter Posts - Yudha Nirmala (Universitas Sebelas Maret, 2020)
ABSTRACTThis research aims to understand the status relation and the way the text and emoji interact in musicians’ twitter posts. This research focuses on the musicians’ twitter posts containing promotion, which also include emoji and text. This research is in a form of a descriptive qualitative which uses the multimodality theory through the generalized image-text relation of Radan Martinec and Andrew Salway. Findings shows that the musicians tend to position the emoji subordinately to text. In terms of logico-semantic relation, the extension relation occurs more than the exemplification relation and enhancement relation. The emoji mostly provides additional information, which cannot be transferred with the text, such as expression and feeling. It is also used to symbolize the event they promote in the post, such as guitar emoji () in a concert promotion. The religious musicians tend to use emoji to provide information about themselves, such as feeling and expression. While, the rock musicians use the emoji more to put information about the event, such as the place and how many days left until the event begins.